P05 Multiple risk behaviour in adolescence and adverse health and social outcomes in early adulthood: findings from a prospective birth cohort study. (2nd September 2017) - Campbell, R; Hickman, M; Kipping, R; Smith, M; Pouliou, T; Heron, J
Abstract : Background: Adolescents engage in new and changed behaviours such as substance use or reduced physical activity. Evidence is accruing that these health risk behaviours co-occur at a population level and cluster within individuals. There has, however, been less focus on what the cumulative impact of engagement in multiple risk behaviours might be even in the short term. We sought to assess if engagement in multiple risk behaviours in mid-adolescence is associated with deleterious health and social outcomes in early adulthood. Methods: 5591 young people enrolled in the Avon Longitudinal Study of Parents and Children provided data on 13 risk behaviours from the domains of physical inactivity, substance use, self-harm, sexual health, vehicle-related risk ehavior, and antisocial ehavior when aged 15 to 16. Logistic regression was used to examine any association between the total number of behaviours engaged in and rates of obesity, harmful alcohol use, problem gambling, anxiety, depression, trouble with the police and unemployment and lack of training at age 18. Results: There was a strong association between multiple risk behaviour and all seven adverse outcomes. For each additional risk behaviour engaged in, the odds of having anxiety or being a problem gambler were 1.18 [1.12, 1.24] and 1.20 [1.13, 1.27] respectively, the odds for depression were 1.24 [1.17, 1.31], and the odds of getting into trouble with the police or of harmful drinking were 1.49 [1.42, 1.57] and 1.58 [1.48, 1.69] respectively. Adjustment for gender, parental socio-economic position, and maternal risk behaviours did little to alter the odds of these adverse outcomes. Confining analyses to adolescents not having experienced the adverse outcomes before age 15, to exclude reverse causality, also produced little change in odds. Conclusion: Improvements in adolscent health are lagging behind those seen in child health. Investment in interventions and environments that effectively prevent multiple risk behaviour is likely to produce better adolescent health and wellbeing.